Uncertainty assessment for a towed underwater stereo PIV system by uniform flow measurement - Bum Woo Han; Jeonghwa Seo; Seung Jae Lee; Dong Myung Seol; Shin Hyung Rhee (International Journal of Naval Architecture and Ocean Engineering, 2018)
The present study aims to assess test uncertainty assessment method of nominal wake field measurement by a Stereoscopic Particle Image Velocimetry (SPIV) system in a towing tank. The systematic uncertainty of the SPIV system was estimated from repeated uniform flow measurements. In the uniform flow measurement case, time interval between image frames and uniform flow speed were varied to examine the effects of particle displacement and flow around the SPIV system on the systematic standard uncertainty. The random standard uncertainty was assessed by repeating nominal wake field measurements and the estimated random standard uncertainty was compared with that of laser Doppler velocimetry. The test uncertainty assessment method was applied to nominal wake measurement tests of a very large crude oil carrier model ship. The nominal wake measurement results were compared with existing experimental database by other measurement methods, with its assessed uncertainty. Keywords: Stereoscopic particle image velocimetry, Towing tank experiment, Test uncertainty